2022
DOI: 10.1155/2022/5081413
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Signature GXYLT2 Is Correlated with Immune Infiltration in Bladder Cancer

Abstract: Background. GXYLT2 (glucoside xylosyltransferase 2) was known as an important gene that regulates classical Notch signaling and is involved in progression in human tumors. However, the correlation between GXYLT2 expression and bladder cancer remains unclear. Methods. GXYLT2 expression was analyzed by ONCOMINE database, GEPIA database, and TIMER database. The Cancer Genome Atlas (TCGA) was utilized to confirm relationships between GXYLT2 and molecular subtypes of BLCA (bladder cancer). We discovered prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Disruption of GR signaling can induce spontaneous gastric inflammation and chemosis in female mice 39 . GXYLT2 is considered an important gene that regulates canonical Notch signaling, participates in human tumor progression, and is closely related to tumor immune infiltrating cells and immune genes 40 , 41 . Zhang et al 42 showed that high levels of TMC5 are activators of PI3K/AKT, RAS/MAPK, and TSC/mTOR, and it has been reported that activation of these pathways may lead to dysregulation of cell survival and ultimately tumorigenesis 43 and various cancers 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of GR signaling can induce spontaneous gastric inflammation and chemosis in female mice 39 . GXYLT2 is considered an important gene that regulates canonical Notch signaling, participates in human tumor progression, and is closely related to tumor immune infiltrating cells and immune genes 40 , 41 . Zhang et al 42 showed that high levels of TMC5 are activators of PI3K/AKT, RAS/MAPK, and TSC/mTOR, and it has been reported that activation of these pathways may lead to dysregulation of cell survival and ultimately tumorigenesis 43 and various cancers 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Glucoside Xylosyltransferase 2 ( gxylt2 ) regulates the activity of the Notch pathway and determines the phosphorylation of MAPK, accelerating cell growth and migration of human cancer cells [ 98 ]. Intriguingly, other studies showed that gxylt2 was correlated to negative prognosis and immune infiltration in bladder cancer [ 99 ], and its methylation was associated with epithelial cells in the inflamed colon of patients suffering from ulcerative colitis [ 100 ]. Transcription elongation factor A (SII)-like 9 ( tceal9 ) and 8 ( tceal8 ) modulate transcription and protein-protein interactions [ 101 ].…”
Section: Exploring Tdark Genes In Duchenne Muscular Dystrophymentioning
confidence: 99%
“…[4] In human bladder cancer, GXYLT2 was closely associated with tumor immune cell infiltration and immune gene expression. [5] In in vitro studies, GXYLT2 overexpression in human breast and gastric cancer cells upregulated Notch/MARK signaling and accelerated cell proliferation and migration. [6] Nonetheless, the prognostic significance and oncogenic role of GXYLT2 in most cancer types remain unclear.…”
Section: Introductionmentioning
confidence: 99%